A Comparative Study of Some Treatment Modalities in Cutaneous Haemangiomas - Jain, P; Sinha, J K (Indian Journal of Plastic Surgery, 1995)
151 children with cutaneous haemangiomas were treated using different treatment modalities and the results were compared. Intralesional triamcinolone was found to be the safest and most effective in strawberry lesions. Cavernous lesions in our study responded best to 50% dextrose injections. A combined approach of oral prednisolone and triamcinolone injections was found to be very useful for mixed lesions.